On coincidence and fixed-point theorems in fuzzy symmetric spaces - T. K. Samanta; B. Dinda; S. Mohinta; S. Roy; J. Ghosh (Journal of Hyperstructures)
In this paper, common fixed point theorems have been studied in fuzzy symmetric space instead of fuzzy metric space.Using weakly compatibility, property ( E.A.), we have generalized the common fixed point theorems for a pair of weakly compatible self mappings, for four self mappings in fuzzy symmetric space. Also we have established the unique common fixed point for four self mappings in this space.